A different world?: the transition experiences of newly qualified children's nurses taking up first destination posts within children's community nursing teams in England. (March 2014) - Darvill, Angela; Fallon, Debbie; Livesley, Joan
<x xml:space="preserve">Abstract</x> The concept of transition is of fundamental concern to those seeking to prepare, recruit, and retain newly qualified staff. The pioneering work of researchers such as Kramer (1974) who explored the transition experiences of nurses has transcended international boundaries (Whitehead & Holmes, 2011) to influence the educational preparation of nurses worldwide. However, much of what we know about the transition experiences of newly qualified nurses is based on research with adult nurses and in the acute care settings. This article outlines the findings from a qualitative study about the experiences of a group of newly qualified children's nurses in England who had taken up first destination posts in community children's nursing teams at a time when such posts were novel, and had previously been met with some resistance. Data were collected using semi-structured interviews and fieldwork observation, and analyzed using a combination of thematic analysis (Braun & Clarke, 2006) and the framework approach (Ritchie & Lewis 2003; Smith & Firth 2011). The findings are outlined under the broad headings of "Shadowing, " "The Visits, " and "Emerging Identity" and support previous research that highlights how good formal support and the physical presence of a preceptor is valued by newly qualified nurses since it reduces occupational stress. However, the study also highlights the downside of such support which occurred because some accepted practices inadvertently reduced confidence and therefore inhibited a smooth transition. The ideal transition experience therefore necessitated a more individual approach, allowing for different rates of progression. The primary care environment allowed for such individuality which may account for the significant finding that the nurses in this study did not report feelings of reality shock (Kramer, 1974) as experienced by those in acute care settings. The study therefore highlights how the development of a new professional identity as a community children's nurse is not just dependent on the actions of the newly qualified nurse, but also of those with whom they work.